Letter - Slyfield, R. W.
034-0096-001 NATIONAL UNION OF CLERKS AND ADMINISTRATIVE WORKERS. Bethnal Green Public Services Branch. Public Health Department, 15 Old Ford Road, Bethnal Green, E.2. 26th October, 1938. The Secretary, National Council of Labour, Transport House, Smith Square, S.W.1. Dear Sir, At a recent meeting of the above Branch the question of supporting an appeal by the International Brigade (Wounded and Dependants Aid Committee) who propose inaugurating a £50,000 National Memorial Fund to meet the future needs of the wounded and the families of those who have fallen in the Spanish war, was under consideration. Our members, while being in entire sympathy with this object, had in mind the extent to which appeals were being duplicated, all having practically the same object in view, and it was thought that the National Memorial Fund should be assisted to a large extent from the Solidarity Fund. I was instructed to enquire whether it is proposed to make a donation from the International Solidarity Fund towards the National Memorial Fund. I shall be glad to hear from you as to this for the information of our members when the question of the above appeal is re-considered by them. Yours faithfully, R.W. Slyfield Branch Secretary. 292/946/34/96